SEMIOTIKA ANALISIS TANDA PADA KARYA DESAIN KOMUNIKASI VISUAL - Tinarbuko, Sumbo (Nirmana, 2003)
The visual communication design works have a sign that has verbal (language) and visual form%2C it is also refer that visual communication design text and its visual offering contents of an icon that has function%2C mainly in a system of non-language to support the message of language%2C so the semiotics approach as a standard analytic method for analyzing the visual communication design works appropriates to be used and responded proactively as same as its contexts. Abstract in Bahasa Indonesia : Karya desain komunikasi visual mempunyai tanda berbentuk verbal (bahasa) dan visual%2C serta merujuk bahwa teks desain komunikasi visual dan penyajian visualnya juga mengandung ikon terutama berfungsi dalam sistem non kebahasaan untuk mendukung pesan kebahasaan%2C maka pendekatan semiotika sebagai sebuah metode analisis tanda guna mengupas karya desain komunikasi visual layak diterapkan dan disikapi secara proaktif sesuai dengan konteksnya. Semiotics%2C A Sign of Analysis%2C Visual Communication Design